Interaction of mercury(II) with humic substances from the Rio Negro (Amazonas State, Brazil) by means of an ion exchange procedure - Rocha, Julio C. [UNESP]; Sene, Jeosadaque J. de [UNESP]; Burba, Peter; Klockow, Dieter (FapUNIFESP (SciELO), 1998)
The aquatic humic substances (HS) investigated in this study with respect to their binding capability towards mercury(II) were isolated from the river Rio Negro, Amazonas State - Brazil, by means of the adsorbent XAD 8. Labile/inert fractions of inorganic Hg(II) complexes formed with these HS were characterized using an ion-exchange batch and column technique, respectively, based on Chelite S. This collector exhibits high Hg(II) distribution coefficients, Kd, up to the order of 104 decreasing, however, in the case of small Hg(II)/HS ratios (< 0.1 μg Hg(II) / mg HS). The influence of different complexation parameters (ratio of Hg(II)/HS, pH, contact time, complexing time) relevant for Hg(II) binding in aquatic environments was assessed. The Hg(II) lability in dissolved HS is mainly influenced by the mass ratio of Hg(II)/HS and the ageing of Hg(II)-HS species formed. This is particularly obvious in the case of low Hg(II) loading of HS where slow transformation processes of freshly formed Hg(II)-HS species significantly decrease their lability, leading to incomplete recoveries (< 20%) of the total Hg(II) bound to HS.
Keywords: Aquatic humic substances; Ion exchange; Mercury(II) speciation; Rio Negro